2021
DOI: 10.1130/g49303.1
|View full text |Cite
|
Sign up to set email alerts
|

Polychromatic polarization: Boosting the capabilities of the good old petrographic microscope

Abstract: Polychromatic polarizing microscopy (PPM) is a new optical technique that allows for the inspection of materials with low birefringence, which produces retardance between 1 nm and 300 nm. In this region, where minerals display interference colors in the near-black to gray scale and where observations by conventional microscopy are limited or hampered, PPM produces a full spectrum color palette in which the hue depends on orientation of the slow axis. We applied PPM to ordinary 30 μm rock thin sections, with pa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…The γ-refraction index is also perpendicular to the growth direction of the prism face. A similar orientation of slow-length axis of the indicatrix has been described very recently sector-zoned garnet crystals from Port Macquarie (Australia) by Cesare et al (2022), showing anomalous birefringence by using polychromatic polarizing microscopy (Shribak 2015(Shribak , 2017. This technique allows elucidation of a very subtle variation of the retardation at low birefringence.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…The γ-refraction index is also perpendicular to the growth direction of the prism face. A similar orientation of slow-length axis of the indicatrix has been described very recently sector-zoned garnet crystals from Port Macquarie (Australia) by Cesare et al (2022), showing anomalous birefringence by using polychromatic polarizing microscopy (Shribak 2015(Shribak , 2017. This technique allows elucidation of a very subtle variation of the retardation at low birefringence.…”
Section: Discussionsupporting
confidence: 67%
“…In Fig. 2d of Cesare et al (2022), it is clearly shown that the slow length is along the growing direction. Although this is interpreted by Cesare et al (2019) as due to a desymmetrization due to cubic to tetragonal change, it might well be related to the kinetic ordering of atoms during the growing of the garnet crystals (probably due to ordering of Fe 2+ at the Y site in the garnet structure) being perhaps related to cyclic chemical zonation along the growing front.…”
Section: Discussionmentioning
confidence: 87%
“…For this purpose, we assume the anisotropy of the garnets to be caused by a tetragonal system. 20,74 Accordingly, the c-axes are oriented 90 • /023 • and 80 • /055 • , which is apparently parallel to the foliation azimuth. This could be explained by domainal growth through epitaxy or topotaxy following the muscovite substrate crystallographic template.…”
Section: Crystal Preferred Orientation Stereonetsmentioning
confidence: 95%
“…18 For example, polychromatic polarised microscopy enables a new use for imaging strained isotropic materials, lowbirefringence minerals, diatom ultrathin sections, 19 and tetragonal garnets in thin sections. 20 Optical whole-slide imaging (WSI) in automated and virtual reality microscopy generates massive datasets fast because image tiles are detected, focussed, and montaged nearly simultaneously. 21 Unlike SEM-based techniques, optical WSI does not need to accumulate and digitise a signal at each pixel as in.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation